Coexistence of multiple leaf nutrient resorption strategies in urban forests - Pin Li; Zejin Wang; Kun Ran (Global Ecology and Conservation)
Rapid urbanization has driven marked changes in local and regional nutrient cycles, thereby influencing the nutrient utilization efficiency of plants proximal to urban areas. Urban forests face substantially higher levels of environmental stress and anthropogenic disturbance than do peri-urban forests owing to the stark variations in environmental parameters observed along urban-periurban-rural gradients. Leaf nutrient resorption is an essential strategy employed by plants to conserve available resources, and three different mechanisms have been shown to be used for the control of such resorption, including nutrient concentration, nutrient limitation, and stoichiometric control. Which of these regulatory strategies are engaged in urban ecosystems and whether several of these strategies coexist in these settings, however, remains uncertain. In this study, leaf samples were collected from 15 common tree species from forest patches in eight parks along urban-rural gradients in the Beijing metropolitan region of China. These samples were used to explore the strategies employed by these plants to control the leaf resorption of carbon (C), nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg). These analyses revealed that nutrient limitation and nutrient concentration control strategies were nutrient-dependent, engaged in the context of N, P, and K resorption, whereas stoichiometric control was involved in the resorption of all analyzed nutrients other than Ca, coexisting with nutrient limitation control. The resorption activity of evergreen needle-leaf trees and ectomycorrhizal trees was found to primarily rely on stoichiometric control rather than nutrient limitation, whereas stoichiometry and nutrient limitation control strategies were both employed by deciduous broadleaf trees and arbuscular mycorrhizal trees, supporting their ability to adapt to changing environmental nutrient availability. Relative to peri-urban forests, urban forests exhibited stronger nutrient limitation control. Elemental variability declined as element concentrations rose in both peri-urban and urban forests, consistent with the relevance of the Stability of Limiting Elements Hypothesis in urban ecosystems. Overall, these data emphasize the fact that multiple nutrient resorption strategies coexist in urban ecosystems, while also supporting the nutrient-dependent nature of these strategies.